The Kwakshua Watersheds Observatory, central coast of British Columbia, Canada. Issue 6 (10th June 2021) - Giesbrecht, Ian J. W.; Floyd, William C.; Tank, Suzanne E.; Lertzman, Ken P.; Hunt, Brian P. V.; Korver, Maartje C.; Oliver, Allison A.; Brunsting, Ray; Sanborn, Paul; Gonzalez Arriola, Santiago G.; Frazer, Gordon W.; St. Pierre, Kyra A.; et al.
Abstract: The Kwakshua Watersheds Observatory (KWO) is an integrative watersheds observatory on the coastal margin of a rain‐dominated bog‐forest landscape in British Columbia (BC), Canada. Established in 2013, the goal of the KWO is to understand and model the flux of terrestrial materials from land to sea – the origins, pathways, processes and ecosystem consequences – in the context of long‐term environmental change. The KWO consists of seven gauged watersheds and a network of observation sites spanning from land to sea and along drainage gradients within catchments. Time‐series datasets include year‐round measurements of weather, soil hydrology, streamflow, aquatic biogeochemistry, microbial ecology and nearshore oceanographic conditions. Sensor measurements are recorded every 5 min and water samples are collected approximately monthly. Additional observations are made during high‐flow conditions. We used remote sensing to map watershed terrain, drainage networks, soils and terrestrial ecosystems. The watersheds range in size from 3.2 to 12.8 km 2, with varying catchment characteristics that influence hydrological and biogeochemical responses. Despite local variation, the overall study area is a global hotspot for yields of dissolved organic carbon, dissolved organic nitrogen and dissolved iron at the coastal margin. This observatory helps fill an important gap in the global network of observatories, in terms of spatial location (central coast of BC), climate (temperate oceanic), hydrology (very high runoff, pluvial regime), geology (igneous intrusive, glacially scoured), vegetation (bog rainforest) and soils (large stores of organic carbon). Abstract : The Kwakshua Watersheds Observatory (KWO) is an integrative watersheds observatory on the coastal margin of a rain‐dominated bog‐forest landscape in British Columbia (BC), Canada. Established in 2013, the goal of the KWO is to understand and model the flux of terrestrial materials from land to sea – the origins, pathways, processes and ecosystem consequences – in the context of long‐term environmental change. The KWO consists of seven gauged watersheds and a network of observation sites spanning from land to sea and along drainage gradients within catchments.